“Us” to co-create value and hate “them” - Itani, Omar S. (2020)
Purpose The purpose of this paper is to understand the role of identity-based relationships, customer brand identification and peer identification, in driving customer outcomes including customer experiential hedonic value, social influence and repurchase intentions through the effects on value co-creation among customers and competitor brand hate, while taking into consideration the moderating impact of individualism. Design/methodology/approach The study integrates social identity theory, identity-based marketing perspective and self-construal theory to develop relationships. The data comprises a web-based survey of customers in the USA and was analyzed using structural equation modeling. Findings Customer brand identification and peer identification are drivers of value co-creation among customers, which leads to favorable outcomes at the customer and brand levels. Customer brand identification drives customers to hate competing brands, which, in turn, motivates customers to exert social influence in favor of their brand and to hold additional repurchase intentions. Customer brand identification and peer identification play different roles in motivating customers to co-create value with their fellows and drive customers to feel hatred toward competing brands contingent on customer individualism. Research limitations/implications Customer brand identification and peer identification play different roles in engaging customers in value co-creation with their peers and competing brands have with their rivals. Individualism self-construal holds a dual role when interacting with customer identification. The study fills multiple gaps in the literature by examining additional effects of customer brand identification and peer identification and exploring a relatively new dimension of the value co-creation process, as well as the role of customers in the competition between brands. Practical implications Brands need to view customers who identify with them as socially active customers capable of participating in value co-creation with other customers and engaging in the rivalry faced by the brands. Moreover, brands are required to build and nurture relationships that are based on social identification to encourage customer brand identification and peer identification which results in favorable customer and business outcomes. Originality/value This study examines the effects of two forms of customer identification on value co-creation between customers and competitor brand hate. In addition, it identifies the dual moderating role of customer individualism on the effects of both social identification forms. The study fills multiple gaps in the literature by understanding new aspects of customer identification, value co-creation and brand hate.